2018
DOI: 10.1002/cbdv.201800319
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Essential Oil Composition, Bioactive Compounds, Anatomical and Antioxidant Activity of Achillea aucheri, an Endemic Species of Iran, at Different Phenological Stages

Abstract: In the present research, the essential oil composition, bioactive compounds, anatomical and antioxidant activity of Achillea aucheri were investigated at four phenological stages. The yield of essential oil ranged from 0.1 % (five leaves appearance stage) to 0.7 % (full flowering stage). So, the oils from the plants harvested at the full flowering stage provided higher essential oil contents than those at other stages. The analysis of the essential oils by GC/MS revealed the presence of a large number of compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 52 publications
(60 reference statements)
1
20
1
Order By: Relevance
“…In previous study, the yield of the volatile oil of A. gypsicola was found to be 0.65 % . On the other hand, the yields of volatile oils in Achillea species have been reported by many investigators range from 0.05 to 2.70 % . According to the average values of reported yields, the oil yields in our samples were above average.…”
Section: Resultscontrasting
confidence: 47%
See 3 more Smart Citations
“…In previous study, the yield of the volatile oil of A. gypsicola was found to be 0.65 % . On the other hand, the yields of volatile oils in Achillea species have been reported by many investigators range from 0.05 to 2.70 % . According to the average values of reported yields, the oil yields in our samples were above average.…”
Section: Resultscontrasting
confidence: 47%
“…In another study, Afshari and Rahimmalek reported that they found different values of antioxidant activity at different growth stages of A. aucheri and while they obtained the highest antioxidant activity at the 50 % flowering stage, they determined the lowest value at 5‐leaf stage. In many studies, it has been reported that the antioxidant capacity of the extracts is thanks to phenolic compounds .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Herbal teas, prepared from some species of this genus, are frequently used for diuretic, abdominal pain, diarrhea, gastric gas and menstruation regulator, wound healing purposes and essential oils and various extracts of these species have been reported to have anti‐inflammatory, analgesic, antimicrobial, antioxidant, spasmolytic, human erythrocyte and leukocyte protective, hemostatic, digestive and cholagogue effects . In addition, Achillea species are used in cosmetics for the production of fragrance and for plant protection in agriculture . A. aleppica DC.…”
Section: Introductionmentioning
confidence: 99%